PERSEPSI DAN SIKAP KELOMPOK TANI HUTAN KEMASYARAKATAN TEBING SIRING TERHADAP PROGRAM KELOMPOK USAHA PERHUTANAN SOSIAL LEBAH MADU - Trisnu Satriadi; Mahrus Aryadi; Hamdani Fauzi (Jurnal Hutan Tropis, 2020)
Apiculture is a program of the Center for Social Forestry and EnvironmentalPartnership Kalimantan for the members of the Community Forestry Farmer Group in Tebing Siring village through the Social Forestry Business Group which began in 2017. The purpose of this research is to determine the perceptions and attitudes of Community Forestry farmer groups on the apiculture program. The results of the study explained that members of the farmer group strongly agreed with the apiculture program, because they profoundly understood honey bee feed cultivation will benefit for the rehabilitation of protected forests and the honey can increase their income. The attitude of members of the farmer group in running the apiculture program is relatively low due to bear pest problems, remote locations, and limited technical coaching. Solutions that can be taken to overcome these problems are pest control, equipment subsidies and kelulut bee cultivation.